A). 3(x + 3) = x − 5


B). 4 − x = (36 – 3x) − (2x + 28)


C). x –



Odpowiedź :

Magda

Odpowiedź:

[tex]a)\\\\3(x+3)=x-5\\\\3x+9=x-5\\\\3x-x=-5-9\\\\2x=-14\ \ /:2\\\\x=-7\\\\\\b)\\\\4-x=(36-3x)-(2x+28)\\\\4-x=36-3x-2x-28\\\\4-x=8-5x\\\\-x+5x=8-4\\\\4x=4\ \ /:4\\\\x=1[/tex]

Zadanie

A)

3(x + 3) = x - 5

3x + 9 = x - 5    l -9

3x = x - 14    l -x

2x = -14    l :2

x = -7

B)

4 - x = (36 - 3x) - (2x + 28)

4 - x = 36 - 3x - 2x - 28

4 - x = 8 - 5x    l -4

-x = 4 - 5x    l +5x

4x = 4    l :4

x = 1